Two new species of Xylocopa (Stenoxylocopa) from southeastern Brazil (Hymenoptera, Apidae) - Melo, Gabriel A. R. (Acta Biológica Paranaense, 2023)
Two new species of Xylocopa (Stenoxylocopa) are described from the highlands of Minas Gerais, in southeastern Brazil: X. urbanae sp. nov. and X. silveirai sp. nov. They stand out from other South American species of X. (Stenoxylocopa) by the quasitridentate mandibles and the dense pilosity covering the metasomal terga.